INOVASI PEMBELAJARAN ILMU FALAK MENGGUNAKAN CODACC LEARNING - fauzi, ahmad (EDUKASIA, 2019)
INNOVATION MODEL ASTRONOMY LEARNING BY CODACC LEARNING Learning model innovation is needed to improve learning outcome. Nowadays, cognitive learning outcome of Astronomy is less satisfactory, it is caused by the incompability of learning models. The use of learning models is still conventional and not constructive. It produce passive learners and unable to build their own knowledge. Therefore, a constructive learning model in Astronomy is crucial. This research employs qualitative method with documentation technique by combining some sources of expert in the field constructivist learning models. The result of this study was to find an approprioriate learning model for Astronomy. The results reveal that Codacc Learning is a learning model intended to make learners that are able to develop their own understanding with discovery, active, cooperative, and contextual learning. The steps of implementing Codacc Learning are developed through some strategies.Keywords:Astronomy; learning model; codacc